Assessing the effectiveness of city-level electric vehicle policies in China. (July 2019) - Qiu, Y.Q.; Zhou, P.; Sun, H.C.
Abstract: Diffusion of electric vehicles (EVs) is regarded as an important strategy for promoting renewable energy development and controlling CO2 emissions in China. Thus, several incentive measures and policies have been released by the pilot cities in China. The question arises as to whether these policies are effective in promoting the EV deployment. This paper assesses the effectiveness of various EV incentive policies at city level by using the data from 88 Chinese pilot cities. Our regression results show a positive relationship between EV sales volume and two demand-side policies: charging discount and infrastructure construction subsidy. However, purchase subsidy policy is found to have no significant effect. Parking benefits policy shows no effect on promoting EV sales. On the other hand, two supply side policies — model development award and manufacturing award — are not effective. We suggest that local governments may keep those two effective policies, phase out the purchase subsidy policy, terminate the parking benefits policy and suspend the model development award policy. The manufacturing award policy can either be paused or be bundled with other regulations or policies that make specific requirements for EV quality. Highlights: The effectiveness of EV policies in China is evaluated at city level. The analysis is conducted with the data from 88 pilot cities in China. Demand side policies are found to be more effective than supply side policies. Charging discount and infrastructure construction subsidy need to be enhanced.